KONTRIBUSI KONSENTRASI, KEKUATAN OTOT LENGAN, KEKUATAN OTOT KAKI, KELENTUKAN PUNGGUNG TERHADAP PUKULAN KE ARAH OUTFIELD OLAHRAGA SOFTBALL - MASHUDA, IBNU; Purnomo, Muhammad (Jurnal Prestasi Olahraga, 2013)
The hitting technique is an important part for getting a score or point the offensive team. There are some main elements thatneed to be considered in making a hit, one of them concentration, arm muscles strenght, leg muscle strenght, and back flexibility. Ifwe do not have the techniques and ways in making hit, it will influence the result of hit, it means that hitter cannot hit toward outfieldarea. Outfield is an area in softball court in the back and only kept by three players so that it is easy toget right hit, we can arrive tobase safely. Hitting is one of technique in softball that is done by offensive team by doing a hit to the ball that is thrown by pitcher.The purpose to get value and save him self or help other runner to reach the next base. The objective of study in this research is todetermine the contribution of concentration, arm muscle strength, leg muscle strength and back flexibility of back for hitting towardoutfield, either individually orsimultaneously (together).The subject of study were softball athletes that consists of 15 people. The method of study used correlational with quantitativeapproach, while the data collection technique in this research is done by doing concentration test, arm muscle strength, leg musclestrength and back flexibility, and hitting toward outfield.Based on the results of analysis, it can be concluded that in this research variables of concentration, arm muscle strength, legmuscle strength and back flexibility individually have significant contribution to the results of a hitting toward outfield in softballPUSLATDA JATIM athletes